Report on the private capital flows and investors' perceptions survey in Trinidad and Tobago 2003 (2003)
Presents information on private capital flows, private sector external debt and Trinidad and Tobago's International Investment Position (IIP).
Keywords: CAPITAL MOVEMENTS